Zika Virus Infection with Prolonged Maternal Viremia and Fetal Brain Abnormalities - Driggers, Rita W; Ho, Cheng-Ying; Korhonen, Essi M; Kuivanen, Suvi; Jääskeläinen, Anne J; Smura, Teemu; Rosenberg, Avi; Hill, D. Ashley; DeBiasi, Roberta L; Vezina, Gilbert; Timofeev, Julia; Rodriguez, Fausto J; et al. (The New England journal of medicine, 2016)
Brief Report: Zika Virus Infection and Fetal Brain Abnormalities In this case report, the association between Zika virus infection and teratogenicity is strengthened, with evidence that the latency period between ZIKV infection of the fetal brain and the detection of microcephaly and intracranial calcifications on ultrasonography may be prolonged. Zika virus (ZIKV), a mosquito-borne flavivirus and member of the Flaviviridae family, was originally isolated from a sentinel primate in Uganda in 1947. 1 ZIKV was associated with mild febrile disease and maculopapular rash in tropical Africa and some areas of Southeast Asia. Since 2007, ZIKV has caused several outbreaks outside its former distribution area in islands of the Pacific: in 2007 on Yap island in Micronesia, in 2013 and 2014 in French Polynesia, and in 2015 in South America, where ZIKV had not been identified previously. 2 – 5 There are separate African and Asian lineages of the virus, 6 and the latter . . .